Variasi Sifat Fisika Tanah pada Berbagai Posisi Lereng di Lahan Agak Curam: Studi Kasus di Kiarapayung, Jatinangor - Setiawan, Ade; Sandrawati, Apong; Arifin, Mahfud; Anindita, Sastrika; Abdurrahman, Mohammad Abyan (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2026)
Topography, particularly slope position, plays an important role in determining soil physical variability, which affects land productivity. This research aims to analyse the effect of slope position on soil physical properties, such as soil texture, bulk density, soil porosity, and soil permeability. Study was conducted in Cilayung village, Jatinangor, Sumedang Regency at ± 850 m asl. We used survey, descriptive, and comparative methods. Stratified sampling was conducted based on three slope positions: upper slope, middle slope, and lower slope. Five samples were collected from each slope position at each sampling site, resulting in a total of 30 samples. Statistical analyses were performed using analysis of variance (ANOVA), followed by Duncan’s multiple range test (DMRT) at a 5% significance level. The results showed that slope position significantly affected the proportions of sand, silt, and clay, as well as soil bulk density and soil permeability. The upper slope had the highest clay content and porosity but exhibited the lowest bulk density and permeability. In contrast, the middle slope had the highest sand content and bulk density, while the highest soil permeability was observed at the lower slope. These findings indicate that slope position is an important factor to consider in conservation-based land management.